PERTIMBANGAN HAKIM ATAS PERUBAHAN STATUS PKWT MENJADI PKWTT DALAM SENGKETA PHK PUTUSAN NOMOR 52/PDT.SUSPHI/2023/PN YYK - Fadilla, Nesha; Kurniawan, Itok Dwi (Verstek, 2025)
This research analyzes how the Panel of Judges determined the change in employment status from a Fixed-Term Employment Agreement (PKWT) to an Indefinite-Term Employment Agreement (PKWTT) in a case of unilateral termination of employment (PHK) by the employer, as ruled in Decision Number 52/Pdt.Sus-PHI/2023/PN Yyk. The research method used is normative legal research. Legal materials were collected through literature and document studies, consisting of both primary and secondary legal sources. The findings reveal that the judges appropriately concluded that the employment relationship between the parties did not fulfill the objective and administrative requirements mandated by legislation. Consequently, the employment agreement was legally transformed into a PKWTT, as regulated in Government Regulation Number 35 of 2021 concerning Fixed-Term Employment Agreements, Outsourcing, Working Hours and Rest Periods, and Termination of Employment. The permanent nature of the work and the absence of PKWT registration served as the legal grounds for the judges to declare that the employment relationship was converted by operation of law into a PKWTT. This decision reflects a commitment to worker protection and demonstrates a progressive and fair interpretation of labor law. Therefore, the judicial considerations in this case are deemed consistent with the principles of legality and protection embedded in Indonesian labor law